Legal Policy Study on the Authority and Responsibility of Nadzir in Waqf Management - Hidayat, Yusup; Machmud, Aris; Lubis, Rahmad (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2024)
Wakf plays a pivotal role in Muslims' economic development and social welfare. The nadir, as the manager of waqf assets, possesses the legal authority and responsibility to optimize waqf utilization in conformity with Sharia principles. Nonetheless, in practice, numerous problems and constraints frequently impede the efficacy of nadzir's job. This article seeks to examine the legal framework governing the power and responsibilities of nadir in waqf administration in Indonesia, intending to identify the support and challenges encountered by nadir in managing waqf assets. This study employs a qualitative methodology utilizing a literature review and a legislative analysis, encompassing an examination of Law No. 41 of 2004 on Waqf and its associated regulations alongside diverse scholarly material pertinent to waqf management. The study's findings suggest that while legal frameworks in Indonesia establish a foundation for nadzir's power, it is necessary to enhance laws and governmental assistance to optimize waqf management. In conclusion, incentive policies and enhanced competence of nadzir are essential to augment efficiency and transparency in waqf management, so enabling a more significant contribution to community welfare.